Collaboration and reflection in the construction of a student model for intelligent computer assisted language learning - Bull, Susan; Pain, Helen; Brna, Paul (1993)
Abstract: "This paper describes the design of an intelligent computer assisted language learning (ICALL) system which focuses on a collaborative student model. The issues involved in this approach are the consideration of the individual learner's language background and learning strategies, and the embedding of this information within a novel, collaborative approach to learner modelling. The student model is based on the notion that a model constructed and repaired through collaboration between the system and student will lead to a more accurate representation of the learner's beliefs, and it is less likely to be regarded with suspicion by the student. Moreover, the act of collaboration will promote learner reflection on both the language to be acquired and the student's approaches to learning. Thus, in addition to being in a position to provide more comprehensive and accurate information to the tutorial module, the student model is also an important learning resource. The theme of learner reflection is further nurtured by an inspectable record of previous versions of the student model, and anticipated future states."
Keywords: Computer software; Education and training; Linguistics; Linguistik; Computer-assisted instruction